Inhibition of PI3K Signalling Selectively Affects Medulloblastoma Cancer Stem Cells. (18th October 2015) - Frasson, Chiara; Rampazzo, Elena; Accordi, Benedetta; Beggio, Giacomo; Pistollato, Francesca; Basso, Giuseppe; Persano, Luca
Abstract : Medulloblastoma is the most common malignant brain tumor of childhood. Although survival has slowly increased in the past years, the prognosis of these patients remains unfavourable. In this context, it has been recently shown that the intracellular signaling pathways activated during embryonic cerebellar development are deregulated in MDB. One of the most important is PI3K/AKT/mTOR, implicated in cell proliferation, survival, growth, and protein synthesis. Moreover, a fraction of MDB cells has been shown to posses stemlike features, to express typical neuronal precursor markers (Nestin and CD133), and to be maintained by the hypoxic cerebellar microenvironment. This subpopulation of MDB cells is considered to be responsible for treatment resistance and recurrence. In this study, we evaluated the effects of PI3K/AKT pathway inhibition on primary cultures of MDB and particularly on the cancer stem cell (CSC) population (CD133 + ). PI3K inhibition was able to counteract MDB cell growth and to promote differentiation of stemlike MDB cells. Moreover, PI3K/AKT pathway suppression induced dramatic cell death through activation of the mitochondrial proapoptotic cascade. Finally, analysis on the stem cells fraction revealed that the MDB CSC population is more sensitive to PI3K targeting compared to the whole cancerous population and its nonstem cell counterpart.